2021
DOI: 10.1039/d1ee02987h
|View full text |Cite
|
Sign up to set email alerts
|

Anionic redox induced anomalous structural transition in Ni-rich cathodes

Abstract: Ni-rich cathodes have emerged as one of the most promising candidates to power next generation electric vehicles. However, they often suffer from poor capacity retention when charged to high voltages...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
51
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 51 publications
(54 citation statements)
references
References 88 publications
3
51
0
Order By: Relevance
“…Liu et al [ 51 ] also revealed a common four-stage structural transition in Ni-rich cathodes by using high throughput operando neutron diffraction. In particular, they found that the Ni-rich cathodes had a universal structural evolution during about 75% delithiation, regardless of the nickel content or the substituent content.…”
Section: Challenges Of Ni-rich Cathode Materials Under High Voltagementioning
confidence: 99%
“…Liu et al [ 51 ] also revealed a common four-stage structural transition in Ni-rich cathodes by using high throughput operando neutron diffraction. In particular, they found that the Ni-rich cathodes had a universal structural evolution during about 75% delithiation, regardless of the nickel content or the substituent content.…”
Section: Challenges Of Ni-rich Cathode Materials Under High Voltagementioning
confidence: 99%
“…For the low-resolution frames (bank 2 and 3), a back-to-back exponential function convoluted with a symmetrical Gaussian function was used to describe the peak profile. For the high-resolution frames (bank 4 and 5), the moderator induced line profile was modeled using a modified Ikeda-Carpenter-David function [51,52]. The Lorenz factor was accounted for by multiplying (d 4 ) [53].…”
Section: Neutron Diffractionmentioning
confidence: 99%
“…First, researchers have mainly focused on the cumulative gas evolution after many cycles or at elevated temperature conditions, but have rarely explored the relationship between oxygen release and gas evolution during a single cycle. [32,33] In fact, when charging to a higher voltage, especially under overcharge conditions, a multitude of reactive oxygen species will appear conspicuously and O 2 will even evolve. [31,[34][35][36] Second, in terms of the analysis of the structural change during the electrochemical process, only some regional measurements that are limited to a certain length scale have been performed, where the local structures of oxygen release are not detected.…”
Section: Introductionmentioning
confidence: 99%